Features of Аgricultural Objects Naming in Ukraine in the Beginning of the XXI Century. - Сидоренко, Олена Миколаївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
The artіcle analyses the names of agricultural objects, which were fixed at the territory of different regions of Ukraine for the last years. Onymian and appellativian are noted as the main ways of ergonyms formation. The ergonyms, formed from onyms and appellatives are conditionally divided into subgroups. Transonymizated antroponyms, mythonyms, toponyms are shown as well as names with ideological and human values; with positive connotation of plants, animals, birds names; fantasy names.